A Multiwavelength Study of a Sample of 70 μm Selected Galaxies in the COSMOS Field. II. The Role of Mergers in Galaxy Evolution - Kartaltepe, Jeyhan S; Sanders, D. B; Le Floc'h, E; Frayer, D. T; Aussel, H; Arnouts, S; Ilbert, O; Salvato, M; Scoville, N. Z; Surace, J; Yan, L; Capak, P; et al. (The Astrophysical journal, 2010)
We analyze the morphological properties of a large sample of 1503 70 mu m selected galaxies in the COSMOS field spanning the redshift range 0.01 < z < 3.5 with a median redshift of 0.5 and an infrared luminosity range of 10(8) < L-IR(8-1000 mu m) < 10(14) L-circle dot with a median luminosity of 10(11.4) L-circle dot. In general, these galaxies are massive, with a stellar mass range of 10(10)-10(12) M-circle dot, and luminous, with -25 < M-K < -20. We find a strong correlation between the fraction of major mergers and L-IR, with the fraction at the highest luminosity (L-IR > 10(12) L-circle dot) being up to similar to 50%. We also find that the fraction of spirals drops dramatically with LIR. Minor mergers likely play a role in boosting the infrared luminosity for sources with low luminosities (L-IR < 10(11.5) L-circle dot). The precise fraction of mergers in any given L-IR bin varies by redshift due to sources at z > 1 being difficult to classify and subject to the effects of bandpass shifting; therefore, these numbers can only be considered lower limits. At z < 1, where the morphological classifications are most robust, major mergers clearly dominate the ULIRG population (similar to 50%-80%) and are important for the LIRG population (similar to 25%-40%). At z > 1, the fraction of major mergers is lower, but is at least 30%-40% for ULIRGs. In a comparison of our visual classifications with several automated classification techniques we find general agreement; however, the fraction of identified mergers is underestimated due to automated classification methods being sensitive to only certain timescales of a major merger. Although the general morphological trends agree with what has been observed for local (U) LIRGs, the fraction of major mergers is slightly lower than seen locally. This is in part due to the difficulty of identifying merger signatures at high redshift. The distribution of the U-V color of the galaxies in our sample peaks in the green valley (< U - V > = 1.1) with a large spread at bluer and redder colors and with the major mergers peaking more strongly in the green valley than the rest of the morphological classes. We argue that, given the number of major gas-rich mergers observed and the relatively short timescale that they would be observable in the (U) LIRG phase, it is plausible for the observed red sequence of massive ellipticals (< 10(12) M-circle dot) to have been formed entirely by gas-rich major mergers.